4k+8(-4-2k)=-2(k-2)

Simple and best practice solution for 4k+8(-4-2k)=-2(k-2) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4k+8(-4-2k)=-2(k-2) equation:


4k+8(-4-2k)=-2(k-2)

We simplify the equation to the form, which is simple to understand
4k+8(-4-2k)=-2(k-2)

Reorder the terms in parentheses
4k+(-32-16k)=-2*(k-2)

Remove unnecessary parentheses
+4k-32-16k=-2+*(+k-2+)

Reorder the terms in parentheses
4k-32-16k=+(-2k+4)

Remove unnecessary parentheses
+4k-32-16k=-2k+4

We move all terms containing k to the left and all other terms to the right.
+4k-16k+2k=+4+32

We simplify left and right side of the equation.
-10k=+36

We divide both sides of the equation by -10 to get k.
k=-3.6

See similar equations:

| 2x+5x-7=4x+11 | | 6ab+2ab-ab= | | 3w+5=l | | 11x^2-13x-4=0 | | -15u-36=-9u-16 | | -5(x-1)-4=5(x+2) | | 10x+4y=492 | | -8.7=7.3-4y | | 8x+32=32x | | 14x+2=100 | | 2m(4m+5)=0 | | 8z-z=-2+2z-2-1 | | x^3+15x^2+26x-175=0 | | 3x+40+x=180 | | 4(k-8)-(9k-9)=-6k | | x^2+y^2=5-k | | ln(6x+11)+ln(x)=ln(10) | | 2u^2-u-1=0 | | 6(a-4)=-3(a-34) | | 8x+8+4x-8+12=8x+42-5x-12 | | 2m(3+4m)+4m=0 | | 8x+3=7(x-4)+5 | | X+40+3x-17+2x-5=180 | | -8.25+-2.75-6= | | x+5+3=9 | | 2ab+4=d | | 2a+8=8 | | 7x-2x=3x+18 | | 7(7-x)=4(x-6) | | 6=-4+8x | | -12x-9=107 | | 8x+2y=1600 |

Equations solver categories